Targeted re-sequencing of a large South African cardiomyopathy cohort - Ndibangwi, Polycarp (Department of Medicine, 2025)
Introduction: Cardiomyopathy is a major cause of heart failure and transplantation globally. In sub Saharan Africa, cardiomyopathies are ranked as the third greatest contributing cause of cardiovascular diseases and account for about 30% of adults hospitalised with heart failure. The prevalence of heart failure due to cardiomyopathies is not well established in the South African population. To address this knowledge gap, we aimed to study the genetic cause of the disease in a large cohort of South African patients with cardiomyopathy. Design: We recruited participants from multiple centres in South Africa and Mozambique between 2015 and 2022. Cases were classified according to phenotypes by a team of experts. Using the Illumina platform, we used targeted sequencing on a panel of 38 known genes that cause primary cardiomyopathies. We used the ACMG classification to investigate class 3, 4 and 5 variants. Variants were validated using Sanger sequencing. Result: We recruited 690 cardiomyopathy probands (594 adults and 96 paediatrics). The 594 adults include dilated cardiomyopathy (n=450), hypertrophic cardiomyopathy (n=60), restrictive cardiomyopathy (n=43) and arrhythmogenic cardiomyopathy (n=41) probands. The adult DCMs constituted 75.8% (450/594) of the IMHOTEP study. The DCM probands had a mean age of 35.6 years at diagnosis, and a 56% preponderance of females were seen; the dominant populations recruited were Black-African (58%) and Mixed ancestry (33%). We reported a diagnostic yield of 16.9% (76/450) for the DCM probands, where 68.4% of the probands had pathogenic TTN truncating variants. The adult HCM cohort constituted 10.1% (60/594) of the IMHOTEP study probands, with a mean age of 41.3 years at diagnosis and a male preponderance of 65%. The dominant populations recruited were 57% Mixed and 25% Black-African. The diagnostic yield for the adult HCM cohort was 23.3% (14/60), with MYH7 (40%) and MYBPC3 (27%) found to be the predominant genes. The adult RCM cohort constituted 7.2% (43/594) of the IMHOTEP study probands, with a mean age of 33.0 years at diagnosis and a 65% female preponderance. The dominant populations recruited were 81% Black-African and 12% Mixed ancestry. We reported a diagnostic yield of 9.3% (4/43) for the RCM probands. The adult ACM cohort constituted 6.9% (41/594) of the IMHOTEP study probands, with a mean age of 40.6 years at diagnosis and a 65.9% male preponderance. The dominant populations recruited were 66% White and 20% Mixed ancestry. We reported a diagnostic yield of 29.3% (12/41), with PKP2 accounting for 62% of the variants. Meanwhile, paediatric probands constituted 13.9% (96/690) of the IMHOTEP study, and 70% were Black-Africans. The diagnostic yield for the paediatric cohort was 2.1% (2/96). Conclusion: This study summarises the findings of the largest cardiomyopathy cohort in Africa. We show a very low genetic yield across all cohorts and that most probands are younger than reported internationally. We also report that DCM has emerged as the dominant phenotype in South Africa. EMF and RCM were categorised as restrictive cardiomyopathies; however, this study identified no single genetic cause in the Mozambique cohort. This study highlights that there is still much work to be done as we have only identified the genetic cause of disease in a small proportion of cardiomyopathy patients.